Manipulation of the cellular microbicidal response and endocytic dynamic by pathogens membrane factors - Benjamin Coiffard (Frontiers Research Topics, 2015)
Intracellular pathogens, such as bacteria and parasites, have evolved specialized mechanisms to survive and replicate in their host, leading to disorders and diseases. The principle of these mechanisms is to reprogram the microbicidal cell function in order to disable the host cells defence that aims to control and eliminate foreign invaders. Devoid of their defence, cells become permissive to pathogens invasion. The aim of this Research Topic is to highlight and cover recent understanding of mechanisms and molecules used by pathogens to interfere with the microbicidal function of cells. This Research Topic will focus on the reprogramming of the cellular dynamics, the immune response, the phagolysosome biogenesis and the signal transduction pathways bypathogens. Special attention will be made on non-proteic virulence factors, however this Research Topic is not restricted to non-proteic virulence factors.